6th Statistics on Health Decision Making: Artificial Intelligence - Authors, Poster Communication (2024)
P01 -  How old are you? Are you a minor? Artificial Intelligence on decision making in Forensic Medicine: Where are we?Valon Nushi, Ana Rodrigues, Arlindo Oliveira, Alexandre Francisco, Rui Santos, Cristiana Palmela Pereira P02 -  Comparison of therapy for vesiculobullous diseases pemphigus/ pemphigoid: observational study at Unidade Local de Saúde Santa Maria (ULS Santa Maria). Diana Augusto, Cristiana Palmela Pereira, Leonor Ferreira, Matilde Martins, Ana Rodrigues, Paulo Filipe, Rui Santos P03 - Dental trauma and forensic medicine: is the civil and labor Portuguese national disability table update?Diana Augusto, Cristiana Palmela Pereira, Carolina Flamino, Francisco Salvado, Francisco Coutinho, Rui Santos P04 - Outpatient oral surgery. Which NSAIDs/analgesics to prescribe? A systematic review and meta-analysis.Ana Rodrigues, Cristiana Palmela Pereira, Madalena M. Tropa, Diana Augusto, Francisco A. Coutinho, Francisco Salvado, Rui Santos P05 - Retrospective analysis of a case series of patients with traumatic injuries to the temporomandibular joint in Hospital Santa Maria: a medico-legal framework for impairment assessmentAna Rodrigues, Cristiana Palmela Pereira, Sofia Matos, Francisco Salvado, Francisco Coutinho, Rui Santos P06 - Analysis of the progression of age-related macular degeneration using the novel variable influence analysis modelJoana D. Martins, Eugénio M. Rocha, Rita A. Coimbra P07 - Evaluation of the antimicrobial resistance in a clinical laboratory: Python software developmentGilberto Rosa, Raquel Diaz, Nadia Kruptsala, Bruno Gago P08 - Perspectives for a conversion model of 2 different OCTA devices in diabetic patients with correlated dataRita Coimbra, Ana R. Santos, Inês Pais, Marta Lopes, Torcato Santos, Chingning T. Yamaguchi, Inês Marques, Elizabeth Pearce P09 - Profile of non-communicable disease risk factors among workers in a higher education institutionMaria Piedade Brandão, Pedro Sá-Couto, Gonçalo Gomes, Pedro Beça P10 - Physical activity and anxiety facing musical performance - an observational study on young musiciansInês Loureiro, Helena Santana, Joaquim Alvarelhão P11 - Machine learning algorithms for enhanced thyroid disease classificationFilipa Santana, Maria da Conceição Costa P12 - Detecting outliers in the clinical pathways of patients with cataractsAlina Humenyuk, Vera Afreixo, Ana H. Tavares, Diogo Raimundo, Heitor Cardoso, Bernardo Marques P13 - Exploring the topological properties of Gait time series as a complementary tool in levodopa dose decision in Parkinson's diseaseJhonathan Barrios, Wolfram Erlhangen, Miguel F. Gago, Estela Bicho, Flora Ferreira P14 - Epidemiological study on central venous catheter infections in a burn unit over three yearsAna Leonor Saraiva, Daniel Ramos P15 - The Importance of measurement scales continuous versus ordinal in model-based clustering methods a case study on maternal health risk dataBlessing U. Ikechukwu, Adelaide Freitas P16 - Extending survival in octogenarian patients through coronary artery bypass grafting: survival analysis using one-sample log-rank testInês Sousa, Sílvia Diaz, Rui J. Cerqueira, Ana Filipa Ferreira, Mário J. Amorim, Paulo Pinho, André P. Lourenço, António S. Barros, Francisca Saraiva, Adelino Leite-Moreira P17 - The significance of assessing proportional hazard assumption in Cox regression to evaluate sex differences after coronary artery bypass graftInês Sousa, Sílvia Diaz, Rui J. Cerqueira, Ana Filipa Ferreira, Mário J. Amorim, Paulo Pinho, André P. Lourenço, António S. Barros, Francisca Saraiva, Adelino Leite-Moreira P18 - Simulating the appointment scheduling in primary care services using Poisson distributionDiana A. Vázquez-Limón, Pedro Damião, Adelaide Freitas, Marco Costa, Nélia da Silva P19 - The effects of regular physical activity on musculoskeletal pain improvement: A cross-sectional studyBeatriz Lau, Arianna Dalponte, Vera Afreixo P20 - Longitudinal analysis of red blood cells omics data from COVID-19 vaccinationCarolina Silva, Joana Saraiva, Cristina Valentim-Coelho, Fátima Vaz, Mohammed H. Semreen, Nelson C. Soares, Deborah Penque, Marília Antunes P21 - Regression trees for analyzing longitudinal health data streams: A comparative studyElsa P. Soares, Inês Sousa P22 - Precision of minimal clinically important improvement (MCII) estimates: comparison of proceduresInês Baptista, Jan T. Kvaløy, Aksel Paulsen, Vera Afreixo, Ingvild Dalen P23 - A method for improving the generation of viral consensus sequences using adaptive modelsMaria João. P. Sousa, Diogo Pratas P24 - Environmental exposure index for early life exposure assessment tool (ELEAT)Beatriz Costa, Lisete Sousa, Célia Rasga, Astrid Vicente P25 - The impact of balance as a marker of health status in patients with LVEF ≤40 participating in a home-based cardiac rehabilitation programmeCarina Rebelo, José. Mesquita Bastos, Vera Afreixo, Ana Abreu P26 - Stratified Cox regression vs. Cox regression with IPW weights: comparing two approaches for the estimation of the effectiveness of COVID-19 seasonal vaccine in the elderly Portuguese populationDiana Lucas, Ausenda Machado, Baltazar Nunes, Vera Afreixo, Patrícia Soares P27 - A Poisson distribution-based simulation approach to consultation scheduling Florbela F. Tavares, Manuel S. Graça, Bruno F. Gago, Pedro D. Rebelo P28 - GeneSEA Explorer: a tool for exploring the depths of gene expression data with Shannon entropy analysisAna M. Gonçalves, Pedro Macedo, Patrício Costa, Nuno S. Osório P29 - Development of a software for metrics analysis in next generation sequencing Pedro Venâncio, Alexandra Lopes, Gabriela Moura P30 - The effects of Prosyntax on children with DLD and ASDMafalda Azevedo, Alexandrina Martins, Tatiana Pereira, Pedro Sá Couto, Marisa Lousada P31 - Mental health, emotion regulation and body-investment in adults with different weight-profilesJoana Henriques, Hugo Senra P32 - Pain and functional capacity in rheumatoid arthritis with acupuncture and complementary treatmentDiana Seixas, Fátima Farinha, Marcos Pacheco da Fonte, Manuel Laranjeira, Marília Rua P33 - Tomographic Image Reconstruction from Projections using Generative AIMaria. V. Reis, Lara Carramate, Silvia De Francesco, Augusto M. F. da Silva P34 - Predicting hospitalization for non-complicated diverticulitis using machine learningRodrigo Antunes, Luís Silva, José Maria Moreira, Susana Ourô, Filipa Fonseca P35 - Potential of machine learning as a predictor of PI-RADS™ v2.1 classificationInês A. Azevedo, Lara Carramate, Silvia De Francesco P36 - The control of dyslipidemia in patients enrolled in a functional unit in northern PortugalMariana C. Correia, Ana D. Fernandes, Mariana V. Martins, Estefânia C. Teixeira, Silvia M. Duarte, Rita F. Ribeiro, Fabíola M. Ferreira, Silvia A. Sousa, Carlota L. Saraiva, Ana C. Barbosa P37 - Psychosocial factors determining mental health status in factory workersÍris M. Milheiro, Lúcia S. Costa, Ana Ferreira, António Loureiro, Sílvia Seco, João P. Figueiredo P38 - Machine learning contribution to detection of subarachnoid hemorrhagic stroke in computed tomographyLeonardo G. Sequeira, Silvia De Francesco, Milton R. Santos P39 - Mental health in students of polytechnic higher educationAna S. Cruz, Lúcia S. Costa, Ana Ferreira, António Loureiro, Sílvia Seco, João P. Figueiredo P40 - Spatial distribution and determinants of TB incidence among children under five-years-old in MozambiqueNelson Cuboia; Joana Reis-Pardal, Ivan Manhiça, Cláudia Mutaquiha, Marla Amaro, Isabel Pfumo-Cuboia, Luís Nitrogénio, Pereira Zindonga, Benedita José, Aleny Couto, Luís Azevedo P41 - Modeling trajectories of peripheral muscle strength, functional capacity and disease impact in COPDJorge Cabral, Guilherme Rodrigues, Joana Antão, Alda Marques P42 - Unraveling the signature of lower airway infection associated with COPD exacerbation in the oral microbiotaInês Henriques, Sara Melo-Dias, Alda Marques, Ana Sousa P43 - Preparing for parenthood during pregnancy – search for health literacy in an E-program at Aveiro municipalityMarília Rua, Marta Silva, Rita Leal; Carlos Ferreira, Inês Rua, Sandra Rodrigues, Joaquim Alvarelhão P44 - The contribution of artificial intelligence in wound healing monitoring: a scoping reviewCarina Marques, Maria B. Fernandes, Mariana Barreiro, Mariana Vilaça, Rafaela Silva, Alexandre Rodrigues P45 - Using AI to support professional interventions in community pharmaciesRúben Duarte Pereira, Joana Pinto, Catarina Nunes, António T. Rodrigues P46 - Flu surveillance in Portugal using over-the-counter sales from community pharmaciesRúben Duarte Pereira, Nuno Rodrigues, Joana Moreno, Zilda Mendes, Rafael Vasconcelos, Gustavo T. Borges, António T. Rodrigues